People Colloquial Vocabulary in Linguistic Creativity was Ukrainian Lesia (on the Material of Poetry). (Linguostylistic Studies, 2014)
The paper analyzes the popular spoken and folk elements in the poetry of Lesya Ukrainka in different years. Colloquial vocabulary in the dictionary of poetic language of the writer is not only seen as a dialect, and more – as commonly used at the time. It was found that the criterion for distinguishing between dialect and folk spoken lexical and lexical and phrase logical facts is the territory of the latter spread beyond the dialect of the array. It was found that the involvement of popular spoken language occurred as a result of direct contact with people – speakers of different dialects, through folklore; an important factor was the «family koine» family Kosachev. The features of the literary treatment of lexical units living national language in linguistic creativity poetess. Key words: popular spoken / folk lexical elements, poetry, spoken language, folk says, yukstapozyt. References